The Status of Semantics in Transformational Generative Grammar (Journal of the College of Basic Education, 2023)
Meaning is one of the problems which seems difficult to deal with tosuch extent that Leonard Bloomfield, who resisted the mentalist approachto language, considered it impossible to define meaning till we have ascientifically accurate knowledge of everything in the speaker’s world.Linguists consider meaning as one of the most complex subjects to dealwith and some of them are in doubt whether meaning can be studiedobjectively and systematically as phonology and grammar or not. Thecomplexity and vagueness of semantics are due to the fact that semanticsis not concerned with one specific field but with various fields such as:philosophy, logic, psychology, anthropology, and sociology. Manylinguists, recently, do their new theory of grammar.This paper is intended to present a brief study of the status of semantics inTransformational generative grammar. It is of three parts: Part One is concerned with the scope of semantics.Part Two presents a historical survey of semantics and its historical development in the schools of grammar.Part Three is a review of the status of semantics in the Transformational schools of grammar.